Corrigendum: Motility increase of Adherent Invasive Escherichia coli (AIEC) induced by a sub-inhibitory concentration of recombinant endolysin LysPA90 (Frontiers in Microbiology, (2022), 13, (1093670), 10.3389/fmicb.2022.1093670) - Hwang, Yoon Jung; Jo, Jaehak; Kim, Eunsuk; Yoon, Hyunjin; Hong, Hyewon; Kim, Min Soo; Myung, Heejoon (Frontiers in Microbiology, 2023)
In the published article, there was an error in the Funding statement. The funding statement for the Korea Health Industry Development Institute (KHIDI) was displayed as: “(HI21C2447010021)”. The correct Funding statement appears below.
Keywords: AIEC; bacteriophage; endolysin; flagella; membrane stress